Identification of nutrients and phytochemicals of raja banana (Musa acuminata) peels extracted with ethanol and acetone solvents and its potential as an anti-obesity agent - Eva Susilawati; Dono Indarto; Tri Nugraha Susilawati (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Banana peel is a waste that has the potential as an anti-obesity agent due to its nutritional and phytochemical content. This study aims to analyze and compare the content of macronutrients, micronutrients, and phytochemical compounds in raja banana peel extracts. The maceration method was performed during the preparation of extracts by using ethanol and acetone solvents. The nutritional and phytochemical contents of the extracts were compared to determine which solvent produced the optimum anti-obesity properties. The ethanol extract consists of water (17,68%), minerals (22,76%), protein (3,50%), carbohydrates (47,98%), and vitamin C (0,82%). The phytochemical content includes flavonoids (73,38 mgQE/g), tannins (0,32%), and chrysin (1,16 mg/L). In conclusion, the ethanol extract of Raja banana peel contains higher nutrients and phytochemicals than the acetone extract, showing greater potential as an anti-obesity agent. Further research is needed to test its bioactivity in vivo or in vitro.